Limited health literacy increases the risk of orthorexia nervosa among urban schoolteachers - Yilmazel, Gulay; Bozdogan, Serpil (Faculty of Medicine, Universitas Trisakti, 2020)
Background Orthorexia nervosa (ON) describes a pathological obsession with proper nutrition that is characterized by a restrictive diet, ritualized patterns of eating, and rigid avoidance of foods believed to be unhealthy or impure. Limited health literacy may play a role in the onset and progression of orthorexia. The aim of this study was to determine the relationship between health literacy and ON among urban schoolteachers.MethodsThis cross-sectional study was conducted in central Black Sea region of Turkey with 420 primary and secondary schoolteachers aged between 18 and 51 years. A questionnaire form including socio-demographic characteristics was used. The Orthorexia Nervosa Questionnaire (ORTO-15) was used to assess orthorexia nervosa behavior and the Turkey Health Literacy Scale (TSOY-32) to assess health literacy. Simple binary and multiple binary logistic regression analyses were carried out to verify the associations between the variables.ResultsOf the study group 46.4% were in the 40-49 year age group, 53.8% were male, 78.6% had ON and 93.6% had limited health literacy. Nearly all of the orthorexics (96.4%) had limited health literacy. Female gender, Instagram use and limited health literacy was significantly associated with ON. Limited health literacy increases the risk of ON 4.85 times among teachers (aOR=4.85;95% C.I. : 2.15-10.94;p=0.000).ConclusionThe current findings suggest that limited health literacy is the strongest risk factor for ON among urban schoolteachers. School health literacy and social media literacy programs can open a new window into revealing ON.